DOI: 10.11606/d.55.2012.tde-06092012-154011
|View full text |Cite
|
Sign up to set email alerts
|

Segurança em sistemas embarcados críticos - utilização de criptografia para comunicação segura

Abstract: AgradecimentosAos meus pais, Agenor e Dinora que nunca mediram esforços para que hoje eu pudesse estar finalizando mais este projeto. Ficam meus agradecimentos pelo apoio moral e financeiro e por acreditarem na minha capacidade de concluir um mestrado. À minha irmã Fernanda e aos demais familiares por terem depositado em mim suas esperanças e por todo apoio moral nestes dois anos.À amizade e orientação da Prof a Dr a Kalinka Regina Lucas Jaquie Castelo Branco, que me acolheu desde o primeiro dia em São Carlos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…"The sender uses the public key of the receiver to encrypt open text in ciphertext and after receiving the resulting ciphertext the receiver uses its private key to decrypt the ciphertext, again retrieving readable text" [17]. In its model it is easy to determine the flow of the encryption and decryption process according to the key creation steps, where encryption occurs, but only the encryption with the key pair (private, public) can be decrypted.…”
Section: Asymmetric Cryptographymentioning
confidence: 99%
“…"The sender uses the public key of the receiver to encrypt open text in ciphertext and after receiving the resulting ciphertext the receiver uses its private key to decrypt the ciphertext, again retrieving readable text" [17]. In its model it is easy to determine the flow of the encryption and decryption process according to the key creation steps, where encryption occurs, but only the encryption with the key pair (private, public) can be decrypted.…”
Section: Asymmetric Cryptographymentioning
confidence: 99%
“…Studies by [34], [35] and [36] showed that codes based on the MIRACL offers better performance than codes based on other cryptographic libraries such as Crypto++, LibTomCrypt, OpenSSL and Lydia+GMP . Regarding MQQ algorithm, was used the version written by [26] in his dissertation.…”
Section: Simulation Environmentmentioning
confidence: 99%